Analysis Of Customer Experience And Customer Engagement In Online Shopping At Shopee Which Impact Customer Satisfaction And Loyalty - Muhammad Fazri Melandri (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to analyze and examine the influence of customer experience and employee engagement on consumer satisfaction and loyalty. This study specifically examines the phenomenon of customer engagement and experience on Shopee E-Commerce. This study uses a quantitative approach using a questionnaire and obtained 260 research respondents. This study uses statistical analysis using the Structural Equation Modeling (SEM) method with Partial Least Square (PLS). The findings of this study indicate that 1) customer experience has a positive and significant effect on customer engagement, satisfaction, and loyalty, 2) Customer engagement has a positive and significant effect on customer satisfaction and loyalty, and 3) Customer satisfaction has a positive and significant effect on customer loyalty. The results of this study indicate that customer experience and employee engagement significantly affect consumer satisfaction and loyalty at Shopee E-Commerce, with customer engagement and satisfaction as key factors in increasing loyalty.